Urgensi Pendidikan bagi Perempuan dalam Perspektif KH. Quraish Shihab - Ulum, M. Bustanul; Jauharoh, Ummu Lum’atil (UAS PRESS, 2023)
The focus of this article is to discuss education for women according to KH. Quraish Shihab. The writing of this article is based on the fact that society currently still places women in a low position, even though many Muslim scientist have actually argued that women have the same position as men. In fact, among urban communities, women have become the driving for social, economic and political change. Meanwhile, it is very sad among rural areas, who position women in a low position. This research managed to get some conclusions. First, women’s education should be more emphasized on the principle of sharing to improve their quality, not for competition between losing or winning. Especially for empowering, increasing strengthening with religious material, which starts early. Second, according to KH. Quraish Shihab women’s education is oriented towards material and immaterial elements. And third, the paradigm map of KH. Quraish Shihab is a critique of conservative groups and liberal groups. Which, education should free women from all actions that oppress themselves as a result of discriminatory ideology adopted by society today, as a reflection of society’s religious interpretation of religious teachings, prioritizing concern for acts of social injustice, lawsuits againts gender discrimination, and social issues